Óleo ozonizado como protocolo dessensibilizante no clareamento dental externo: estudo clínico, randomizado e duplo-cego. - Wiggers, Iara Fretta (2022)
Post-bleaching sensitivity is the most common side effect of in-office tooth whitening. For this reason, several products have been introduced to provide greater comfort to patients during and after the bleaching procedure. Objectives: To evaluate the action of ozonized oil associated with an obliterating desensitizing agent in reducing post-dental bleaching sensitivity. Methodology: Forty patients with dental saturation A2 or more were selected and divided into two groups according to the desensitizing agent used: control group (GC) - potassium nitrate and sodium fluoride and treatment group (TG) - sunflower oil ozonized and glutaraldehyde. In-office bleaching was performed with 35% hydrogen peroxide in a single clinical session lasting 45 minutes. The following variables were evaluated: I – intensity of sensitivity at different times in the same group; II – intensity of sensitivity at different times in different groups; III- global sensitivity, recorded by patients with the aid of a visual analog scale during the entire time the whitening gel was in contact with the teeth; IV - worse pain and V - color change, which was evaluated at the beginning of treatment and one week after the end of the treatment with the help of a VITA color scale. The risk analysis of tooth sensitivity of both groups was compared using McNemar's exact test. To analyze the intensity of tooth sensitivity, the Wilcoxon and Friedman tests were used. Results: In the statistical analysis of global sensitivity, statistically significant differences were found at 35 and 40 minutes, between the scores for the treatment and control groups. Conclusion: The use of an association protocol between glutaraldehyde and ozonated oil prior to tooth bleaching was effective in reducing dentin sensitivity at 35 and 40 minutes when compared to the control group.